Perioperative Practices and Outcome of Neurosurgery during the COVID-19 Pandemic: Institutional Experience and Retrospective Observational Analysis - Khurana, Priyanka; Ganjoo, Pragati; Duggal, Sakshi; Kiro, Kiran Lata; Dhanwani, Lavina; Tandon, Monica S.; Singh, Daljit; Jagetia, Anita (Indian Journal of Neurosurgery, 2021)
Introduction Surgery during the coronavirus disease 2019 (COVID-19) pandemic is a major concern due to possibility of infection transmission among health care workers (HCWs) and patients, and a worsened surgical outcome; most surgeries are thus being deferred. However, we continued with emergency neurosurgeries using our own Neurosurgical Standard Operating Procedures (NS-SOPs). We describe here our institutional neurosurgical experience and observations of a retrospective analysis done to determine the incidence of workplace-acquired COVID infection among the HCWs, and the outcome of neurosurgery performed during the early phase of the on-going pandemic.Methods Our NS-SOPs included a Screening Proforma, and protocols for the conduct of neurosurgery, starting from the preoperative period till death or postdischarge follow-up of the patients. Protocols to ensure safety and mental well-being of the HCWs were also implemented. Patient and HCW data from April 1 to August 31, 2020 was collected and analyzed for the postsurgical patient outcome and for determining the level of workplace-transmitted COVID infection.Results Neurosurgeries were performed on 169 patients during this 5-month period. We observed a cumulative mortality of 17/169 (10.1%), with 5 patients having unexplained postoperative respiratory manifestations and rapid deterioration suggestive of COVID illness. Nineteen HCWs (8.83%), mostly nurses, were infected, but only 3 (16.7%) had workplace-acquired infection. The infections were sporadic with no cluster of infections observed.Conclusion Implementation of standard perioperative protocols and their continuous scrutiny, evaluation, and modification is important to contain infection in HCWs and to improve the neurosurgical outcome during this pandemic.
Keywords: perioperative protocols in COVID-19; neurosurgery practices and outcome; health care worker infection